A Response - Hutchinson, Roger (Toronto journal of theology, 1991)
The editors have offered us the opportunity to comment briefly on the criticisms of our book appearing in this issue (see Lee Cormie's "The Option for the Poor and Oppressed in Doing Social Ethics," P. Travis Kroeker's "Pluralism and Policy Monism: The Political Irrelevance of Theology," and Janet Silman's "An Open Letter to Cranford Pratt and Roger Hutchinson"). We welcome the invitation. Although we shall identify points which we think misrepresent our position, our main concern is to clarify the differences which do exist between us and these critics. In doing this we will concentrate primarily on Lee Cormie's article, since in contrast to the other two, it invites response rather than repentance.